Inheritance of seed iron and zinc concentrations in common bean (Phaseolus vulgaris L.) - Blair, Matthew W.; Astudillo, Carolina; Grusak, M.A.; Graham, R; Beebe, Stephen E. (Springer, 2009)
Micronutrients are essential elements needed in small amounts for adequate human nutrition and include the elements iron and zinc. Both of these minerals are essential to human well-being and an adequate supply of iron and zinc help to prevent iron deficiency anemia and zinc deficiency, two prevalent health concerns of the developing world. The objective of this study was to determine the inheritance of seed iron and zinc accumulation in a recombinant inbred line (RIL) population of common beans from a cross of low × high mineral genotypes (DOR364 × G19833) using a quantitative trait locus (QTL) mapping approach. The population was grown over two trial sites and two analytical methods (Inductively Coupled Plasma Spectrometry and Atomic Absorption Spectroscopy) were used to determine iron and zinc concentration in the seed harvested from these trials. The variability in seed mineral concentration among the lines was larger for iron (40.0–84.6 ppm) than for zinc (17.7–42.4 ppm) with significant correlations between trials, between methods and between minerals (up to r = 0.715). A total of 26 QTL were identified for the mineral × trial × method combinations of which half were for iron concentration and half for zinc concentration. Many of the QTL (11) for both iron (5) and zinc (6) clustered on the upper half of linkage group B11, explaining up to 47.9% of phenotypic variance, suggesting an important locus useful for marker assisted selection. Other QTL were identified on linkage groups B3, B6, B7, and B9 for zinc and B4, B6, B7, and B8 for iron. The relevance of these results for breeding common beans is discussed especially in light of crop improvement for micronutrient concentration as part of a biofortification program.